Persepsi dan Preferensi Pengunjung Terhadap Kenyamanan dan Aktivitas Skateboarding di Taman Bung Karno Tabanan - Putra, Agung Wahana; Sugianthara, Anak Agung Gede; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2023)
Tabanan is one of the regencies in the province of Bali. The city also has a city park which is named Taman Bung Karno Tabanan. This park certainly has recreational activities in it, one of which is extreme sports such as skateboarding. However, this activity is considered to interfere with park visits, judging from the issues that say that skaters often damage public paving and planter facilities and also disrupt the circulation of park visitor activities. This is the background for the author to raise the issue as research material, with the aim of this study being to find out the perceptions and preferences of park visitors and skaters, so as to obtain solutions to overcome the problems of visitor comfort and skateboarding activities. The research method used is a survey method with data collection techniques through observation, interviews, questionnaires, and literature study. Based on the results of the study, visitors rated the level of comfort at the Bung Karno Tabanan City Park as adequate with a percentage of 49.9% with a preference of park visitors of 72.1% wanting the addition of skateboard facilities. Suggestions that can be given to increase comfort at Taman Bung Karno Tabanan is that there is a need for additional skateboarding sports facilities or can be relocated to a more appropriate place.